Karakteristik Pasien Demam Berdarah Dengue Rawat Inap di Rumah Sakit Umum UKI Tahun 2020 - Diah putri Ayu Islammia; Nanda Aula Rumana; Laela Indawati; Deasy Rosmala Dewi (Yayasan Literasi Sains Indonesia, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus (DEN) which is spread through mosquito bites. This research is a quantitative descriptive study using a non-random sampling method with a saturated sample technique. The study was conducted at the UKI General Hospital with a sample of 94 patients. The results showed that the age of the most patients was 17-25 years, 30 patients (32%), the most gender were male (60%), domiciled in East Jakarta (70%), the most occupations were self-employed (36%), months The highest incidence was in March 23 patients, the most felt symptom was fever (100%), the highest severity level based on the ICD-10 code was A97.0 94 patients (100%), the category of platelet count when it arrived was abnormal (93 %), while the category of the number of platelets at home is normal (10%), the category of the number of hematocrit is abnormal (43%), while the category of the number of hematocrit when going home is normal (51%), the ICD-10 code used is A91 , the longest length of hospitalization was <6 days 67 patients (71%). The condition when he returned home was healed (99%).